Gluing characteristics of Papua New Guinea timber species for various non-structural applications - Belleville, Benoit; Lancelot, Kilva; Galore, Elaine; Fehrmann, Johannes; Ozarska, Barbara (Maderas. Ciencia y Tecnología, 2023)
Papua New Guinea (PNG) has abundant natural forest resources but there are many constraints which need to be addressed to support the development of competitive value-added wood industries. There is a need to develop knowledge and capacity in wood science and processing technologies which support successful domestic value-adding wood processing enterprises. A comprehensive testing program has been developed to assess the glue‐bond strength and performance of selected commercial PNG timber species in various cli- matic conditions to simulate service conditions in potential market destinations. Two criteria namely shear strength and wood failure have been used to determine if a species can meet the minimum requirements for either dry use or wet use applications. The performance of 24 different PNG commercial timber species has been assessed using a one-component cross-linking polyvinyl acetate emulsion adhesive. The bondability of the selected species has been carefully estimated considering the wood density and wood moisture content for the strength and durability in dry- and wet-use conditions. The testing results show that as the wood density as a wood property factor and moisture content as a service condition factor increase, high shear strength with high wood failure become more difficult to achieve consistently. The highest shear strength and wood failure results were achieved by softwood plantation species and low-density hardwood species. Based on the testing results, the selected species have been classified into bondability classes (bond very well, bond well, bond with difficulty, very difficult to bond).